How do stream and depth affect rowing? - Dudhia, A.
This Web FAQ page has been prompted by a discussion on rec.sport.rowing relating to the why rowing upstream or downstream should feel different, and also the difference between deep/shallow water. Content: 1. Introduction 2. Viscosity 3. Boat Resistance 4. River Flow 5. Upstream/Downstream Resistance 6. Shallow Water Resistance 7. Upstream/Downstream Times